Funcionalización in situ y post-síntesis de nanofibras electrohiladas para la producción de materiales avanzados - Pérez Nava, Alejandra (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
Nanofiber constructs are of great interest in the development of innovative materials for a wide range of industrial and technological applications. In this sense, electrospinning is the most straightforward approach that allows the fabrication of nanofibers. Electrospun nanofibers have facilitated the design of novel materials, whose main advantages are related to their unique properties conferred by their nano-scale dimensions. Nonetheless, the development of advanced materials makes imperative the study of strategies that allow for the functionalization of nanostructured polymeric materials through physical and chemical approaches in order to enhance their applications. With the aim to contribute to the progress of methodologies that allow the development of specialized electrospun nanofibrous materials, in the present investigation strategies such as the functionalization of as-spun nanofiber mats during the production stage and post-electrospinning are analyzed. In the case of post-electrospinning functionalization, heterostructured materials composed by poly(vinyl alcohol)/poly(3,4-ethylenedioxythiophene):perchlorate (NF-PVA/PEDOT:ClO4-) have been produced through PEDOT electropolymerization onto PVA nanofibrous mats surface. The non-covalent immobilization of PEDOT:ClO4- displays reversible electrochemical properties that underscores its potential application for the production of energy storage materials. Regarding to post-electrospinning covalent functionalization, hybrid biomaterials composed by chitosan nanofibers/collagen (NF-CTS/COL) and poly(vynil alcohol)/collagen (NF-PVA/COL) have been developed through covalent conjugation of collagen (COL). The achievement of these biomimetic materials has been accomplished via amidation and esterification reactions respectively, enabled by carbodiimides. Both bioconjugation reactions propose innovative alternatives that allow the incorporation of COL avoiding its solubilization. COL solubilization involves its denaturalization and decreases its bioactivity, disadvantages related not only by collagen’s electrospinning but also by common processing procedures.

Las colecciones de nanofibras son de gran interés en el desarrollo de novedosos materiales con una amplia variedad de aplicaciones tecnológicas e industriales. La técnica de electrohilado es la estrategia más adecuada para la producción de nanofibras ya que facilita el diseño de nuevos materiales con propiedades únicas que surgen como resultado de sus dimensiones nanométricas. Sin embargo, el diseño de materiales avanzados hace imperativo el estudio de estrategias que permitan el perfeccionamiento de los materiales poliméricos nanoestructurados mediante procedimientos físicos y químicos que potencialicen sus aplicaciones. Con el propósito de contribuir al desarrollo de metodologías que favorezcan el desarrollo de materiales avanzados constituidos por nanofibras, en la presente investigación se analizan estrategias de funcionalización de colecciones de nanofibras durante la etapa de producción y posterior al electrohilado. En términos de funcionalización post-electrohilado, se han obtenido materiales heteroestructurados compuestos por nanofibras de alcohol polivinílico/poli(3,4-etilendioxitiofeno):perclorato (NF-PVA)/PEDOT:ClO4- mediante la electropolimerización del polímero conductor PEDOT sobre colecciones de NF-PVA. La inmovilización no covalente de PEDOT:ClO4- sobre la matriz de NF-PVA induce un comportamiento electroquímico reversible que favorece su potencial aplicación en el desarrollo de materiales para el almacenamiento de energía. Por su parte, mediante la funcionalización covalente post-electrohilado se han preparado biomateriales híbridos compuestos por nanofibras de quitosano/colágeno (NF-CTS/COL) y nanofibras de PVA/colágeno (NF-PVA/COL) bajo el esquema de conjugación covalente de COL. La obtención de los materiales biomiméticos se ha realizado mediante reacciones de amidación y esterificación respectivamente, asistidas con carbodiimidas. Estas estrategias de bioconjugación representan una novedosa alternativa que permite la incorporación de COL sin requerir su solubilización; evitando así su desnaturalización y el deterioro de la bioactividad de COL, riesgo implicado durante su procesamiento mediante electrohilado y otros métodos.
Instituto de Investigaciones Químico Biológicas. Doctorado en Ciencias Químicas
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5605; info:eu-repo/classification/cti/2; IIQB-R-D-2021-0254; Electrohilado; Materiales avanzados; Biomateriales